Ferrite particles and method for producing the same
A dry mixing process using molybdenum compounds facilitates the production of ferrite particles with controlled size and shape, addressing the limitations of conventional methods and enhancing magnetic properties for noise suppression and electromagnetic shielding applications.
Patent Information
- Application Number
- JP2023545201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-07-29
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-07-29
AI Technical Summary
Conventional methods for producing ferrite particles face challenges in controlling particle size and achieving uniform size distribution, leading to difficulties in meeting the requirements of various applications, particularly in noise suppression sheets for vehicles and communication devices.
The production of ferrite particles involves a dry mixing process using a molybdenum compound as a flux, allowing for the formation of ferrite particles with controlled particle size and distribution, enhanced magnetic properties, and a spinel structure, achieved through a method that includes mixing metal and iron compounds with molybdenum compounds and firing at specific temperatures.
The method enables the production of high-quality ferrite particles with controlled shape and reduced aggregation, exhibiting improved magnetic performance and suitability for applications in noise suppression and electromagnetic shielding.
Smart Images

Figure 0007605328000002 
Figure 0007605328000003 
Figure 0007605328000004
Abstract
Description
[Technical field]
[0001] The present invention relates to ferrite particles and a method for producing ferrite particles. [Background technology]
[0002] Ferrite is a compound oxide whose main component is iron oxide (Fe2O3), and is used in various fields, mainly as a magnetic material. In recent years, the demand for noise suppression sheets has been expanding due to the increasing density of electromagnetic environments inside automobiles and other vehicles caused by the electrification of these vehicles. Currently, most noise suppression sheets are for car navigation systems and in-vehicle cameras, but demand for millimeter wave radars is expected in the future. In addition, in the communications field, with the shift to 5G, there is an increasing demand for high shielding performance in noise suppression sheets for smartphones.
[0003] In Patent Document 1, an aqueous solution containing a hexagonal ferrite precursor is heated to 300° C. or higher and pressurized to 20 MPa or higher to convert the precursor into hexagonal ferrite, thereby obtaining a hexagonal ferrite having the general formula AFe 12 O 19 The present invention discloses a method for producing a hexagonal ferrite powder, which produces a ferrite represented by the following formula: In addition, the invention discloses that A in the above general formula is a divalent metal atom, and the divalent metal atom is a metal atom that can become a divalent cation as an ion, and includes alkaline earth metal atoms such as barium, strontium, calcium, and the like, and lead, and the like.
[0004] Patent Document 2 discloses a method for producing hexagonal ferrite magnetic powder, which comprises melting a raw material mixture containing a glass-forming component and a hexagonal ferrite-forming component, rapidly cooling the resulting melt to obtain a solid, and heat-treating the resulting solid to precipitate hexagonal ferrite magnetic particles and glass components. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-222517 A [Patent Document 2] JP 2020-100561 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, knowledge about conventional ferrite particles and their manufacturing methods is limited, and there is still room for further study. In addition, conventional methods for manufacturing ferrite particles usually use a wet process or a sol-gel reaction, and since it is difficult to control the particle size in the wet process or the sol-gel reaction, it is difficult to obtain ferrite particles having a predetermined particle size or a predetermined particle size distribution according to the application.
[0007] The present invention has been made to solve the problems described above, and has an object to provide ferrite particles having excellent properties and a method for easily producing such ferrite particles. [Means for solving the problem]
[0008] As a result of intensive research aimed at solving the above problems, the inventors discovered that by using a molybdenum compound as a flux, ferrite particles can be easily produced by dry mixing, and that ferrite particles containing molybdenum can be easily produced, thereby completing the present invention. That is, the present invention has the following aspects.
[0009] [1] Ferrite particles containing molybdenum.
[0010] [2] Ferrite particles according to the above [1], having a spinel structure.
[0011] [3] The ferrite particles according to [2] above, wherein the spinel structure is represented by AFe2O4 (wherein A is one or more elements selected from Ni, Mn, Cu, Zn, Mg, Ca, and Co).
[0012] [4] The ferrite particles according to the above [1] or [2], wherein the molybdenum content in the ferrite particles is determined by XRF analysis of the ferrite particles, and is a content (Mo1) calculated as MoO3 relative to 100 mass% of the ferrite particles, of 0.1 to 30 mass%.
[0013] [5] The ferrite particles according to the above [1] or [2], wherein the molybdenum content in the surface layer of the ferrite particle is 2.0 to 95.0 mass% in terms of MoO3 content (Mo2) relative to 100 mass% of the surface layer of the ferrite particle, as determined by XPS surface analysis of the ferrite particle.
[0014] [6] The ferrite particles according to the above [1] or [2], wherein the molybdenum is unevenly distributed in a surface layer of the ferrite particles.
[0015] [7] The ferrite particles according to the above [1] or [2], wherein a surface distribution ratio of molybdenum (Mo2 / Mo1), which is the content (Mo2) in terms of MoO3 relative to 100 mass% of the surface layer of the ferrite particle determined by XPS surface analysis of the ferrite particle, is 1.0 to 80.0, where Mo2 / Mo1 is the content (Mo1) in terms of MoO3 relative to 100 mass% of the ferrite particle determined by XRF analysis of the ferrite particle, and Mo2 is the content (Mo2) in terms of MoO3 relative to 100 mass% of the surface layer of the ferrite particle determined by XPS surface analysis of the ferrite particle.
[0016] [8] The ferrite particles according to the above [1] or [2], wherein the average particle size of the primary particles of the ferrite particles is 0.1 to 100 μm.
[0017] [9] The specific surface area measured by the BET method is between 0.1 and 2.5 m 2 The ferrite particles according to the above [1] or [2], wherein the molecular weight of the ferrite particles is 1000 or more.
[0018]
[10] A method for producing the ferrite particles according to the above [1], comprising calcining a metal compound and an iron compound in the presence of a molybdenum compound.
[0019]
[11] A method for producing ferrite particles according to the above
[10] , comprising adding a zinc compound to the metal compound and the iron compound in the presence of the molybdenum compound, and calcining the mixture.
[0020]
[12] The method for producing ferrite particles according to the above
[10] or
[11] , wherein the molybdenum compound is at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate and sodium molybdate.
[0021]
[13] The method for producing ferrite particles according to the above
[10] or
[11] , wherein the sintering temperature is 800 to 1500°C. Effect of the Invention
[0022] According to the present invention, it is possible to provide ferrite particles having excellent properties and a method for easily producing the ferrite particles. [Brief description of the drawings]
[0023] [Figure 1] 1 is a SEM image of the ferrite particles obtained in Example 1. [Diagram 2] 1 is a SEM image of the ferrite particles obtained in Example 2. [Diagram 3] 1 is a SEM image of the ferrite particles obtained in Example 3. [Figure 4] 1 is a SEM image of the ferrite particles obtained in Example 4. [Diagram 5] 1 is a SEM image of the ferrite particles obtained in Example 5. [Figure 6] 1 is a SEM image of the ferrite particles obtained in Example 6. [Figure 7] 1 is a SEM image of ferrite particles obtained in Example 7. [Figure 8] 1 is a SEM image of ferrite particles obtained in Example 8. [Figure 9] 1 is a SEM image of ferrite particles obtained in Example 9. [Figure 10] 1 is a SEM image of ferrite particles obtained in Example 10. [Figure 11] 1 is a SEM image of ferrite particles obtained in Example 11. [Figure 12] 1 is a SEM image of ferrite particles obtained in Comparative Example 1. [Figure 13] 1 shows X-ray diffraction (XRD) patterns of the ferrite particles obtained in Examples 1 to 10 and Comparative Example 1. [Figure 14] 1 is an X-ray diffraction (XRD) pattern of the ferrite particles obtained in Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.
[0025] Ferrite particles The ferrite particles of the embodiment contain molybdenum. The ferrite particles of the embodiment contain molybdenum and have excellent properties such as magnetism derived from molybdenum. Moreover, the ferrite particles of the embodiment can have an excellent property that the particle shape is controlled. Furthermore, the ferrite particles of the embodiment may have excellent properties such as low degree of agglomeration or no agglomeration.
[0026] The ferrite particles of the embodiment may contain molybdenum derived from a molybdenum compound used in the manufacturing method described below. In addition, by using a molybdenum compound in the manufacturing method described below, it is possible to control the particle shape of the manufactured ferrite particles.
[0027] The state and amount of molybdenum contained in the ferrite particles of the embodiment are not particularly limited, and may be contained in the ferrite particles as molybdenum metal, molybdenum oxide, a partially reduced molybdenum compound, etc. Molybdenum is considered to be contained in the ferrite particles as MoO3, but may also be contained in the ferrite particles as MoO2, MoO, etc. other than MoO3.
[0028] The form in which molybdenum is contained is not particularly limited, and may be contained in a form in which it is attached to the surface of the ferrite particle, may be contained in a form in which it is substituted as part of the crystal structure of the ferrite particle, may be contained in an amorphous state, or may be a combination of these.
[0029] In this manner, the ferrite particles of the embodiment can contain molybdenum, and in particular can contain molybdenum derived from the molybdenum compound used in the manufacturing method described below, and therefore improved magnetic performance can be expected compared to conventional ferrite particles.
[0030] In this specification, controlling the particle shape of ferrite particles means that the particle shape of the produced ferrite particles is not amorphous. In this specification, ferrite particles with a controlled particle shape mean ferrite particles whose particle shape is not amorphous. The ferrite particles of the embodiment may have a polygonal shape. The ferrite particles of the embodiment may have a controlled crystal shape and have an idiomorphic polygonal shape. The ferrite particles with a controlled crystal shape can be manufactured by the manufacturing method described below.
[0031] The aggregate (powder) of ferrite particles may contain ferrite particles of shapes other than polygonal in any state. The content of polygonal ferrite particles is preferably 80% or more by weight or number based on the total amount of the aggregate (powder) of ferrite particles, more preferably 90% or more, and even more preferably 95% or more. The morphology of the ferrite particles can be confirmed by a scanning electron microscope (SEM).
[0032] In the manufacturing method of the ferrite particles according to the embodiment, the particle size and molybdenum content of the obtained ferrite particles can be controlled by controlling the amount and type of the molybdenum compound used, the firing temperature, and the like in the manufacturing method described below.
[0033] The average particle size of the primary particles of the ferrite particles in the embodiment may be 0.1 to 100 μm, 0.1 to 50 μm, 1.0 to 40 μm, or 1.5 to 30 μm.
[0034] The average particle size of the primary particles of ferrite particles is determined by photographing the ferrite particles with a scanning electron microscope (SEM) and measuring the maximum length between two points on the contour line of 50 randomly selected primary particles (i.e., primary particles) in the two-dimensional image.
[0035] The median diameter D of the ferrite particles of the embodiment calculated by a laser diffraction / scattering method 50 The thickness may be 0.5 to 50 μm, 1 to 40 μm, or 1.5 to 35 μm.
[0036] The median diameter D of ferrite particles calculated by the laser diffraction / scattering method 50 can be calculated as the particle size at which the volume cumulative percentage is 50% in the particle size distribution measured in a dry state using a laser diffraction particle size distribution analyzer.
[0037] The specific surface area of the ferrite particles according to the embodiment, as determined by the BET method, is 0.1 to 2.5 m 2 / g, and 0.15 to 2.5m 2 / g, and may be 0.1 to 2.0m 2 / g, and may be 0.2 to 2.0m 2 / g.
[0038] The specific surface area is measured using a specific surface area meter (e.g., BELSORP-mini, manufactured by Microtrack-Bell Corporation), and the surface area per 1 g of the sample measured from the amount of nitrogen gas adsorbed by the BET method (Brunauer-Emmett-Teller method) is defined as the specific surface area (m 2 / g).
[0039] The ferrite particles of the embodiment contain ferrite. The ferrite particles can have various crystal structures such as a spinel structure and a garnet structure, but in this embodiment, it is preferable that the ferrite particles have a spinel structure. The spinel structure is represented, for example, by AFe2O4 (wherein A is one or more elements selected from Ni, Mn, Cu, Zn, Mg, Ca, and Co). Typically, the spinel structure is represented by AFe2O4 (wherein A is one or two elements selected from Ni, Mn, Cu, Zn, Mg, Ca, and Co).
[0040] The ferrite particles of the embodiment preferably contain 65 to 99.95 mass % of AFe2O4, more preferably 70 to 99.5 mass %, and even more preferably 90 to 99 mass %, relative to 100 mass % of the ferrite particles.
[0041] The ferrite particles may contain nickel. The nickel content in the ferrite particles can be measured by XRF analysis. The nickel content in the ferrite particles of the embodiment is preferably 5 to 50 mass%, more preferably 10 to 40 mass%, and even more preferably 15 to 30 mass%, in terms of NiO content (Ni1) relative to 100 mass% of the ferrite particles, determined by XRF analysis of the ferrite particles.
[0042] The iron content in the ferrite particles can be measured by XRF analysis. The iron content in the ferrite particles of the embodiment is preferably 35 to 80 mass%, more preferably 40 to 75 mass%, and even more preferably 45 to 70 mass%, in terms of Fe2O3 content (Fe1) relative to 100 mass% of the ferrite particles, as determined by XRF analysis of the ferrite particles.
[0043] The molybdenum content in the ferrite particles can be measured by XRF analysis. The molybdenum content in the ferrite particles of the embodiment is preferably 0.1 mass% or more, more preferably 0.1 to 30 mass%, more preferably 0.5 to 25 mass%, and even more preferably 0.75 to 20 mass%, in terms of MoO3 content (Mo1) relative to 100 mass% of the ferrite particles, determined by XRF analysis of the ferrite particles.
[0044] In the ferrite particles of the embodiment, the upper and lower limit values of the above-mentioned content (Ni1), content (Fe1) and content (Mo1) can be freely combined. In addition, the values of the content (Ni1), content (Fe1) and content (Mo1) can also be freely combined.
[0045] As an example of the ferrite particles of the embodiment, when the spinel structure is represented by NiFe2O4, the ferrite particles are subjected to XRF analysis, and the ferrite particles are subjected to XRF analysis. The ferrite particles may have a Ni1 content of 15 to 45 mass%, a Fe1 content of 35 to 75 mass%, and a Mo1 content of 0.1 to 30 mass%, The ferrite particles may have a Ni1 content of 17.5 to 40 mass%, a Fe1 content of 40 to 70 mass%, and a Mo1 content of 0.5 to 25 mass%, The ferrite particles may have a content (Ni1) of 20 to 35 mass %, a content (Fe1) of 45 to 65 mass %, and a content (Mo1) of 0.75 to 20 mass %.
[0046] The ferrite particles may further contain zinc. The zinc content in the ferrite particles can be measured by XRF analysis. The zinc content in the ferrite particles of the embodiment is preferably 0.5 to 25 mass%, more preferably 0.75 to 20 mass%, and even more preferably 0.1 to 15 mass%, in terms of ZnO2 content (Zn1) relative to 100 mass% of the ferrite particles, determined by XRF analysis of the ferrite particles.
[0047] In the ferrite particles of the embodiment, the upper and lower limit values of the above-mentioned content (Ni1), content (Fe1), content (Zn1) and content (Mo1) can be freely combined. In addition, the values of the content (Ni1), content (Fe1), content (Zn1) and content (Mo1) can also be freely combined.
[0048] As an example of the ferrite particles of the embodiment, when the spinel structure is represented by NiFe2O4, the ferrite particles are subjected to XRF analysis, and the ferrite particles are subjected to XRF analysis. The ferrite particles may have a content (Ni1) of 10 to 40 mass%, a content (Fe1) of 45 to 60 mass%, a content (Zn1) of 0.5 to 20 mass%, and a content (Mo1) of 0 to 5 mass%, The ferrite particles may have a Ni1 content of 12.5 to 35 mass%, an Fe1 content of 47.5 to 57.5 mass%, a Zn1 content of 0.75 to 17.5 mass%, and a Mo1 content of 0.1 to 3 mass%, The ferrite particles may have a (Ni1) content of 15 to 30 mass%, a (Fe1) content of 50 to 55 mass%, a (Zn1) content of 1.0 to 15 mass%, and a (Mo1) content of 0.5 to 2.5 mass%.
[0049] The ferrite particles may contain manganese instead of nickel. The manganese content in the ferrite particles can be measured by XRF analysis. The manganese content in the ferrite particles of the embodiment is preferably 10 to 60 mass%, more preferably 20 to 50 mass%, and even more preferably 30 to 40 mass%, in terms of MnO2 content (Mn1) relative to 100 mass% of the ferrite particles, determined by XRF analysis of the ferrite particles.
[0050] In the ferrite particles of the embodiment, the upper and lower limit values of the contents (Mn1), (Fe1) and (Mo1) exemplified above can be freely combined. The values of the contents (Mn1), (Fe1) and (Mo1) can also be freely combined.
[0051] As an example of the ferrite particles of the embodiment, when the spinel structure is represented by MnFe2O4, the ferrite particles are subjected to XRF analysis, and the ferrite particles are subjected to XRF analysis. The ferrite particles may have a content (Mn1) of 10 to 60 mass%, a content (Fe1) of 30 to 80 mass%, and a content (Mo1) of 0 mass%, The ferrite particles may have a content (Mn1) of 20 to 50 mass%, a content (Fe1) of 40 to 75 mass%, and a content (Mo1) of 0 mass%, The ferrite particles may have a content (Mn1) of 30 to 40 mass %, a content (Fe1) of 50 to 70 mass %, and a content (Mo1) of 0 mass %.
[0052] For the above-mentioned XRF analysis, an X-ray fluorescence analyzer (for example, Primus IV manufactured by Rigaku Corporation) can be used.
[0053] The content (Ni1) in terms of NiO refers to the value obtained from the amount of NiO converted by using a calibration curve in terms of NiO to convert the nickel content determined by XRF analysis of ferrite particles.
[0054] The content (Fe1) in terms of Fe2O3 refers to the value obtained from the amount of Fe2O3 converted by using a calibration curve in terms of Fe2O3 to convert the iron content determined by XRF analysis of ferrite particles.
[0055] The content (Mo1) calculated as MoO3 refers to the value obtained from the amount of MoO3 calculated by converting the molybdenum content determined by XRF analysis of ferrite particles using a calibration curve calculated as MoO3.
[0056] The content (Zn1) in terms of ZnO2 refers to the value obtained from the amount of ZnO2 calculated by converting the zinc content determined by XRF analysis of ferrite particles using a calibration curve in terms of ZnO2.
[0057] The content (Mn1) calculated as MnO2 refers to the value obtained from the amount of MnO2 calculated by using a calibration curve for MnO2 conversion to obtain the manganese content determined by XRF analysis of ferrite particles.
[0058] The nickel content in the surface layer of the ferrite particle can be measured by XPS (X-ray photoelectron spectroscopy) surface analysis. The nickel content in the surface layer of the ferrite particle of the embodiment is preferably 0 to 65 mass%, more preferably 0 to 60 mass%, and even more preferably 0 to 55 mass%, in terms of NiO content (Ni2) relative to 100 mass% of the surface layer of the ferrite particle, as determined by XPS surface analysis of the ferrite particle.
[0059] The iron content in the surface layer of the ferrite particle can be measured by XPS (X-ray photoelectron spectroscopy) surface analysis. The iron content in the surface layer of the ferrite particle of the embodiment is preferably 5 to 65 mass%, more preferably 10 to 60 mass%, and even more preferably 12.5 to 57.5 mass%, in terms of Fe2O3 content relative to 100 mass% of the surface layer of the ferrite particle, as determined by XPS surface analysis of the ferrite particle.
[0060] The molybdenum content in the surface layer of the ferrite particle can be measured by XPS (X-ray photoelectron spectroscopy) surface analysis. The molybdenum content in the surface layer of the ferrite particle of the embodiment is preferably 1 mass% or more, more preferably 2.0 to 95 mass%, more preferably 2.5 to 90 mass%, and even more preferably 3.0 to 87.5 mass%, in terms of MoO3 content (Mo2) relative to 100 mass% of the surface layer of the ferrite particle, as determined by XPS surface analysis of the ferrite particle.
[0061] In the ferrite particles of the embodiment, the upper and lower limit values of the above-mentioned contents (Ni2), (Fe2), and (Mo2) can be freely combined. The values of the contents (Ni2), (Fe2), and (Mo2) can also be freely combined.
[0062] As an example of the ferrite particles of the embodiment, when the spinel structure is represented by NiFe2O4, the following is obtained by subjecting the ferrite particles to XPS surface analysis: The ferrite particles may have a Ni2 content of 0 to 60 mass%, an Fe2 content of 5 to 65 mass%, and a Mo2 content of 2.5 to 90 mass%, The ferrite particles may have a Ni2 content of 3 to 57.5 mass%, an Fe2 content of 10 to 60 mass%, and a Mo2 content of 5 to 87.5 mass%, The ferrite particles may have a content (Ni2) of 5 to 55 mass %, a content (Fe2) of 12.5 to 55 mass %, and a content (Mo2) of 7.5 to 85 mass %.
[0063] As described above, the ferrite particles may further contain zinc. The zinc content of the ferrite particles can be measured by XPS (X-ray photoelectron spectroscopy) surface analysis. The zinc content of the surface layer of the ferrite particles of the embodiment is preferably 0.1 to 10 mass%, more preferably 0.25 to 8 mass%, and even more preferably 0.5 to 6 mass%, in terms of ZnO2 content (Zn2) relative to 100 mass% of the surface layer of the ferrite particles, as determined by XPS surface analysis of the ferrite particles.
[0064] In the ferrite particles of the embodiment, the upper and lower limit values of the above-mentioned contents (Ni2), (Fe2), (Zn2), and (Mo2) can be freely combined. The values of the contents (Ni2), (Fe2), (Zn2), and (Mo2) can also be freely combined.
[0065] As an example of the ferrite particles of the embodiment, when the spinel structure is represented by NiFe2O4, the following is obtained by subjecting the ferrite particles to XPS surface analysis: The ferrite particles may have a content (Ni2) of 0.5 to 25 mass%, a content (Fe2) of 20 to 70 mass%, a content (Zn2) of 0.1 to 10 mass%, and a content (Mo2) of 20 to 75 mass%, The ferrite particles may have a content (Ni2) of 1.0 to 20 mass%, a content (Fe2) of 25 to 65 mass%, a content (Zn2) of 0.25 to 8 mass%, and a content (Mo2) of 25 to 70 mass%, The ferrite particles may have a (Ni2) content of 1.5 to 10 mass%, a (Fe2) content of 30 to 60 mass%, a (Zn2) content of 0.5 to 6 mass%, and a (Mo2) content of 30 to 65 mass%.
[0066] In addition, when the ferrite particles contain manganese instead of nickel, the manganese content in the ferrite particles can be measured by XPS (X-ray photoelectron spectroscopy) surface analysis. The content in the surface layer of the ferrite particles of the embodiment is preferably 10 to 80 mass%, more preferably 20 to 70 mass%, and even more preferably 30 to 60 mass%, as a content (Mn2) calculated as MnO2 relative to 100 mass% of the surface layer of the ferrite particles, which is determined by XPS surface analysis of the ferrite particles.
[0067] In the ferrite particles of the embodiment, the upper and lower limit values of the contents (Mn2), (Fe2), and (Mo2) exemplified above can be freely combined. The values of the contents (Mn2), (Fe2), and (Mo2) can also be freely combined.
[0068] As an example of the ferrite particles of the embodiment, when the spinel structure is represented by MnFe2O4, the following is obtained by subjecting the ferrite particles to XPS surface analysis: The ferrite particles may have a content (Mn2) of 10 to 80 mass%, a content (Fe2) of 5 to 75 mass%, and a content (Mo2) of 10 to 95 mass%, The ferrite particles may have a content (Mn2) of 20 to 70 mass%, a content (Fe2) of 7.5 to 65 mass%, and a content (Mo2) of 12.5 to 90 mass%, The ferrite particles may have a (Mn2) content of 30 to 60 mass %, a (Fe2) content of 10 to 60 mass %, and a (Mo2) content of 15 to 87.5 mass %.
[0069] For the above-mentioned XPS analysis, a scanning X-ray photoelectron spectrometer (for example, QUANTERA SXM manufactured by ULVAC-PHI, Inc.) can be used.
[0070] The above content (Ni2) refers to the value obtained by performing XPS surface analysis of the ferrite particles using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element, converting the nickel content into oxide, and calculating the NiO content relative to 100% by mass of the surface layer of the ferrite particles.
[0071] The above content (Fe2) refers to the value obtained by performing XPS surface analysis of the ferrite particles using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element, converting the iron content into oxide, and determining the Fe2O3 content relative to 100% by mass of the surface layer of the ferrite particles.
[0072] The above content (Mo2) refers to the value obtained by performing XPS surface analysis of the ferrite particles using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element, converting the molybdenum content into an oxide, and calculating the MoO3 content relative to 100% by mass of the surface layer of the ferrite particles.
[0073] The above content (Mn2) refers to the value obtained by performing XPS surface analysis of the ferrite particles using X-ray photoelectron spectroscopy (XPS) to obtain the abundance ratio (atom%) of each element, converting the manganese content into an oxide, and determining the MnO2 content relative to 100% by mass of the surface layer of the ferrite particles.
[0074] In the ferrite particle of the embodiment, the molybdenum is preferably unevenly distributed in a surface layer of the ferrite particle.
[0075] Here, in this specification, the term "surface layer" refers to a region within 10 nm from the surface of the ferrite particle of the embodiment. This distance corresponds to the detection depth of the XPS used for measurement in the examples.
[0076] Here, "distributed unevenly in the surface layer" refers to a state in which the mass of molybdenum or molybdenum compounds per unit volume in the surface layer is greater than the mass of molybdenum or molybdenum compounds per unit volume in areas other than the surface layer.
[0077] In the ferrite particles of this embodiment, the fact that molybdenum is concentrated on the surface layer of the ferrite particles can be confirmed by the fact that the molybdenum content (Mo2) in MoO3 equivalent relative to 100% by mass of the surface layer of the ferrite particles, determined by XPS surface analysis of the ferrite particles, is greater than the molybdenum content (Mo1) in MoO3 equivalent relative to 100% by mass of the ferrite particles, determined by XRF (X-ray fluorescence) analysis of the ferrite particles, as shown in the examples described below.
[0078] In the ferrite particles of the embodiment, as an indicator that molybdenum is concentrated in the surface layer of the ferrite particles, the ferrite particles of the embodiment have a surface distribution ratio of molybdenum (Mo2 / Mo1), which is the content (Mo2) in terms of MoO3 relative to 100 mass% of the surface layer of the ferrite particle, determined by XPS surface analysis of the ferrite particles, of 1.0 to 80, more preferably 3.0 to 60, and even more preferably 5.0 to 50, relative to the content (Mo1) in terms of MoO3 relative to 100 mass% of the ferrite particle.
[0079] By distributing molybdenum or a molybdenum compound unevenly on the surface layer of the ferrite particles, excellent properties such as catalytic activity can be imparted more efficiently than when molybdenum or a molybdenum compound is present not only on the surface layer but also uniformly in the non-surface layer (inner layer).
[0080] The ferrite particles of the embodiment can be provided as an aggregate of ferrite particles, and for example, the nickel content, iron content, and molybdenum content values described above can be values determined using the aggregate as a sample. Similarly, the nickel content, iron content, zinc content, and molybdenum content values described above can be values determined using the aggregate as a sample. Furthermore, the manganese content, iron content, and molybdenum content values described above can be values determined using the aggregate as a sample.
[0081] The ferrite particles of the present embodiment may further contain lithium, potassium, or sodium in addition to molybdenum.
[0082] <Method of manufacturing ferrite particles> The method for producing ferrite particles according to the embodiment includes calcining a metal compound and an iron compound in the presence of a molybdenum compound. More specifically, the method for producing ferrite particles according to the embodiment may include mixing the metal compound, the iron compound, and the molybdenum compound to form a mixture, and calcining the mixture.
[0083] By calcining the metal compound and the iron compound in the presence of a molybdenum compound, the reaction efficiency of ferrite particle production can be improved compared to the case where a molybdenum compound is not used, so that high-quality ferrite particles with reduced impurity content can be efficiently produced, and further, ferrite particles with low degree of aggregation can be easily produced.
[0084] The metal compound may be a metal compound containing any element selected from Ni, Mn, Cu, Zn, Mg, Ca, and Co. Examples of the metal compound include nickel compounds, manganese compounds, copper compounds, zinc compounds, magnesium compounds, calcium compounds, and cobalt compounds.
[0085] In addition, by adding a zinc compound to the metal compound and iron compound in the presence of the molybdenum compound and then calcining the mixture, it is possible to add a certain proportion of a paramagnetic material, thereby appropriately reducing the magnetism of the A site and enhancing the magnetism resulting from the interaction of the AB site.
[0086] In addition, the use of a compound containing molybdenum and nickel, such as nickel molybdate, is also considered to be the use of a molybdenum compound and a nickel compound.
[0087] According to the method for producing ferrite particles of the embodiment, the ferrite particles of the embodiment described above can be easily produced.
[0088] A preferred method for producing ferrite particles includes a step of mixing a metal compound containing any one of elements selected from Ni, Mn, Cu, Zn, Mg, Ca, and Co, an iron compound, and a molybdenum compound to obtain a mixture (mixing step), and a step of firing the mixture (firing step). Hereinafter, a case where a nickel compound is used as an example of the metal compound will be described.
[0089] [Mixing process] The mixing step is a step of mixing a nickel compound, an iron compound, and a molybdenum compound to obtain a mixture. The contents of the mixture will be described below.
[0090] (Nickel compounds) The type of the nickel compound is not particularly limited. For example, the nickel compound may be nickel hydroxide, nickel oxide, nickel carbonate, nickel molybdate, nickel chloride, nickel nitrate, nickel sulfate, nickel acetate, etc., of which nickel oxide, nickel hydroxide, and nickel carbonate are preferred, and nickel oxide or nickel hydroxide are more preferred from the viewpoint of reactivity and the absence of harmful gases.
[0091] Since the shape of the ferrite particles after sintering hardly reflects the shape of the raw material nickel compound, for example, spherical, amorphous, high aspect structures (wires, fibers, ribbons, tubes, etc.), sheets, etc. can be suitably used as the nickel compound.
[0092] (Iron Compounds) The type of iron compound is not particularly limited, and known compounds can be used. Specific examples of these include iron oxide (II) (FeO), so-called wustite, black iron oxide (II,III) (Fe3O4), and reddish-brown iron oxide (III) (Fe2O3). Examples of iron oxide (III) include α-Fe2O3, β-Fe2O3, γ-Fe2O3, and ε-Fe2O3. Examples of iron oxyhydroxide include α-iron oxyhydroxide, β-iron oxyhydroxide, γ-iron oxyhydroxide, δ-iron oxyhydroxide, and the like. Examples of iron hydroxide include iron hydroxide (II) (Fe(OH)2) and iron hydroxide (III) (Fe(OH)3). As the iron oxide, iron oxide (III) (Fe2O3) is preferred.
[0093] The shape of the iron compound is not particularly limited, but for example, a spherical, rod-like or plate-like shape can be suitably used.
[0094] (Molybdenum Compounds) Examples of the molybdenum compound include molybdenum oxide, molybdic acid, molybdenum sulfide, molybdenum silicide, and molybdate compounds, with molybdenum oxide and molybdate compounds being preferred.
[0095] The molybdenum oxide includes molybdenum dioxide (MoO2), molybdenum trioxide (MoO3), etc., with molybdenum trioxide being preferred.
[0096] The molybdate compound is MoO4 2- , Mo2O7 2- , Mo3O 10 2- , Mo4O 13 2- , Mo5O16 2- , Mo6O 19 2- , Mo7O 24 6- , Mo8O 26 4- The molybdenum oxoanion may be, but is not limited to, a salt compound of the molybdenum oxoanion such as those mentioned above. The molybdenum oxoanion may be an alkali metal salt, an alkaline earth metal salt, or an ammonium salt.
[0097] The molybdate compound is preferably an alkali metal salt of a molybdenum oxoanion, more preferably lithium molybdate, potassium molybdate or sodium molybdate, even more preferably potassium molybdate or sodium molybdate, and particularly preferably sodium molybdate.
[0098] In the method for producing ferrite particles of this embodiment, the molybdate compound may be a hydrate.
[0099] The molybdenum compound is preferably at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate, and sodium molybdate, more preferably at least one compound selected from the group consisting of molybdenum trioxide, potassium molybdate, and sodium molybdate, and further preferably molybdenum trioxide and / or sodium molybdate.
[0100] (Zinc compounds) In the mixing step, the nickel compound, the iron compound, and the molybdenum compound may be mixed together, and a zinc compound may be further added to obtain a mixture. The type of the zinc compound is not particularly limited. For example, the zinc compound may be zinc hydroxide, zinc oxide, zinc carbonate, zinc molybdate, zinc acetate, zinc chloride, zinc nitrate, zinc sulfate, etc., and zinc hydroxide or zinc oxide is preferred from the viewpoint of reactivity and the absence of harmful gases.
[0101] (Manganese compounds) In the mixing step, a manganese compound may be used instead of the nickel compound, and the manganese compound, the iron compound, and the molybdenum compound may be mixed to form a mixture. The type of the manganese compound is not particularly limited. For example, the manganese compound may be manganese carbonate, manganese oxide, manganese acetate, manganese chloride, manganese nitrate, manganese sulfate, or hydrates thereof. Manganese carbonate or manganese oxide is preferred from the viewpoint of reactivity and from the viewpoint of not generating irritating gases.
[0102] The method for producing ferrite particles according to the embodiment may include a step of calcining a nickel compound and an iron compound in the presence of a molybdenum compound and a sodium compound and / or a potassium compound.
[0103] The method for producing ferrite particles of the embodiment may include a step (mixing step) of mixing a nickel compound, an iron compound, a molybdenum compound, and a sodium compound and / or a potassium compound to form a mixture prior to the firing step, and may include a step (firing step) of firing the mixture.
[0104] In the manufacturing method of the embodiment, by using a sodium compound and / or a potassium compound, it is easy to adjust the particle size of the ferrite particles produced, and it is possible to produce ferrite particles with little or no aggregation.
[0105] Here, at least a part of the molybdenum compound and the sodium compound may be replaced with a compound containing molybdenum and sodium, such as sodium molybdate, and at least a part of the molybdenum compound and the potassium compound may be replaced with a compound containing molybdenum and potassium, such as potassium molybdate. Therefore, a process of mixing a nickel compound, an iron compound, and a compound containing molybdenum and potassium and / or sodium to obtain a mixture is also considered to be a process of mixing a nickel compound, an iron compound, a molybdenum compound, and a potassium compound and / or a sodium compound to obtain a mixture.
[0106] In addition, a compound containing molybdenum and sodium suitable as a fluxing agent can be produced, for example, in the process of firing using a molybdenum compound and a sodium compound, which are less expensive and more readily available, as raw materials. Here, the use of a molybdenum compound and a sodium compound as fluxing agents and the use of a compound containing molybdenum and sodium as fluxing agents are both considered to be the use of a molybdenum compound and a sodium compound as fluxing agents, i.e., in the presence of a molybdenum compound and a sodium compound.
[0107] A compound containing molybdenum and potassium suitable as a fluxing agent can be produced, for example, in the firing process using a molybdenum compound and a potassium compound, which are cheaper and more readily available, as raw materials. Here, the use of a molybdenum compound and a potassium compound as fluxing agents and the use of a compound containing molybdenum and potassium as fluxing agents are both considered to be the use of a molybdenum compound and a potassium compound as fluxing agents, i.e., in the presence of a molybdenum compound and a potassium compound.
[0108] The above-mentioned molybdenum compounds may be used alone or in combination of two or more kinds.
[0109] In addition, sodium molybdate (Na2Mo n O 3n+1 , n=1 to 3) contains sodium and can therefore function as a sodium compound, which will be described later.
[0110] In addition, potassium molybdate (K2Mo n O 3n+1, n=1 to 3) contains potassium and can therefore also function as a potassium compound, which will be described later.
[0111] (Sodium compounds) The sodium compound is not particularly limited, but examples thereof include sodium carbonate, sodium molybdate, sodium oxide, sodium sulfate, sodium hydroxide, sodium nitrate, sodium chloride, metallic sodium, etc. Among these, it is preferable to use sodium carbonate, sodium molybdate, sodium oxide, and sodium sulfate from the viewpoints of industrial ease of availability and ease of handling.
[0112] The above-mentioned sodium compounds may be used alone or in combination of two or more kinds.
[0113] As described above, sodium molybdate contains molybdenum and can therefore function as the molybdenum compound described above.
[0114] (Potassium compounds) The potassium compound is not particularly limited, but includes potassium chloride, potassium chlorite, potassium chlorate, potassium sulfate, potassium hydrogen sulfate, potassium sulfite, potassium hydrogen sulfite, potassium nitrate, potassium carbonate, potassium hydrogen carbonate, potassium acetate, potassium oxide, potassium bromide, potassium bromate, potassium hydroxide, potassium silicate, potassium phosphate, potassium hydrogen phosphate, potassium sulfide, potassium hydrogen sulfide, potassium molybdate, potassium tungstate, etc. In this case, the potassium compound includes isomers, as in the case of molybdenum compounds. Among these, it is preferable to use potassium carbonate, potassium hydrogen carbonate, potassium oxide, potassium hydroxide, potassium chloride, potassium sulfate, and potassium molybdate, and it is more preferable to use potassium carbonate, potassium hydrogen carbonate, potassium chloride, potassium sulfate, and potassium molybdate.
[0115] The potassium compounds described above may be used alone or in combination of two or more kinds.
[0116] As described above, potassium molybdate contains molybdenum and can therefore function as the molybdenum compound described above.
[0117] In the method for producing ferrite particles according to the embodiment, a preferable combination of raw materials is, when the spinel structure of the ferrite particles is represented by NiFe2O4, nickel oxide, iron (III) oxide, and molybdenum trioxide. Similarly, a preferred combination of raw materials in the method for producing ferrite particles according to the embodiment includes nickel oxide, iron (III) oxide, and sodium molybdate or a hydrate thereof. Similarly, a preferred combination of raw materials in the method for producing ferrite particles according to the embodiment includes nickel oxide, iron (III) oxide, molybdenum trioxide, and sodium molybdate or a hydrate thereof. Similarly, a preferred combination of raw materials in the method for producing ferrite particles according to the embodiment includes nickel oxide, iron (III) oxide, zinc oxide, molybdenum trioxide, and sodium molybdate or a hydrate thereof.
[0118] In addition, a preferred combination of raw materials in the manufacturing method of ferrite particles according to the embodiment is, when the spinel structure of the ferrite particles is represented by MnFe2O4, the combination includes manganese carbonate or a hydrate thereof, iron oxyhydroxide, and sodium molybdate or a hydrate thereof.
[0119] By calcining a nickel compound and an iron compound in the presence of a molybdenum compound and a sodium compound, or in the presence of a molybdenum compound and a potassium compound, it is easy to adjust the particle size of the ferrite particles produced, and it is possible to produce ferrite particles with little or no aggregation. The reason for this is not clear, but the following reasons are considered. For example, K2MoO4 and Na2MoO4 are stable compounds and are difficult to volatilize in the calcination process, so they are unlikely to undergo rapid reactions in the volatilization process, making it easy to control the growth of ferrite particles. In addition, it is thought that the molten K2MoO4 and Na2MoO4 function like a solvent, and the particle size value can be increased, for example, by extending the reaction time. In addition, it is thought that the molten K2MoO4 and Na2MoO4 function like a solvent, so that the ferrite particles are dispersed and aggregation is unlikely to occur.
[0120] In the method for producing ferrite particles of this embodiment, a molybdenum compound is used as a fluxing agent. In the present specification, this method for producing ferrite particles using a molybdenum compound as a fluxing agent may be simply referred to as a "flux method". It is considered that, after the nickel compound, the iron compound, and the molybdenum compound react with each other at high temperatures by the firing to form iron molybdate and nickel molybdate, the iron molybdate and nickel molybdate are further decomposed into nickel-iron double oxide and molybdenum oxide at a higher temperature, and the molybdenum compound is taken into the ferrite particles. The molybdenum oxide is sublimated and removed from the system, and during this process, the molybdenum compound is reacted with the nickel-iron double oxide to form a molybdenum compound on the surface layer of the ferrite particles. Regarding the mechanism of formation of the molybdenum compounds contained in the ferrite particles, more specifically, it is believed that Mo-O-Ni and Mo-O-Fe are formed on the surface layer of the ferrite particles through a reaction between molybdenum and nickel atoms and iron atoms, and that when sintered at high temperatures, Mo is released and molybdenum oxide or compounds having Mo-O-Ni-O-Fe bonds are formed on the surface layer of the ferrite particles.
[0121] Molybdenum oxide that is not incorporated into the ferrite particles can be recovered and reused by sublimation, which reduces the amount of molybdenum oxide that adheres to the surfaces of the ferrite particles and maximizes the inherent properties of the ferrite particles.
[0122] On the other hand, the alkali metal salt of the molybdenum oxoanion does not vaporize even at the calcination temperature range and can be easily recovered by washing after calcination. This reduces the amount of molybdenum compounds released outside the calcination furnace, and also allows for a significant reduction in production costs.
[0123] In the above flux method, for example, when a molybdenum compound and a sodium compound are used in combination, it is believed that the molybdenum compound and the sodium compound react to form sodium molybdate. At the same time, it is believed that the molybdenum compound reacts with an iron compound to form iron molybdate. Then, for example, nickel molybdate and iron molybdate are decomposed in the presence of liquid-phase sodium molybdate, and crystal growth is caused, so that ferrite particles with low or no aggregation can be easily obtained while suppressing the evaporation of the above flux (sublimation of MoO3).
[0124] (Other metal compounds) Other metal compounds can be used during firing as desired. The method for producing ferrite particles according to the embodiment can include a step (mixing step) of mixing a nickel compound, an iron compound, and a molybdenum compound with a sodium compound and / or a potassium compound and other metal compounds to form a mixture prior to the firing step, and can include a step (firing step) of firing the mixture.
[0125] The other metal compound is not particularly limited, but preferably contains at least one selected from the group consisting of Group II metal compounds and Group III metal compounds.
[0126] Examples of the Group II metal compound include calcium compounds, strontium compounds, and barium compounds.
[0127] Examples of the Group III metal compound include a scandium compound, an yttrium compound, a lanthanum compound, and a cerium compound.
[0128] The above-mentioned other metal compounds refer to oxides, hydroxides, carbonates, and chlorides of metal elements. For example, yttrium compounds include yttrium oxide (Y2O3), yttrium hydroxide, and yttrium carbonate. Of these, the other metal compounds are preferably oxides of metal elements. These other metal compounds include isomers.
[0129] Among these, the metal compounds of the third periodic elements, the metal compounds of the fourth periodic elements, the metal compounds of the fifth periodic elements, and the metal compounds of the sixth periodic elements are preferred, the metal compounds of the fourth periodic elements and the metal compounds of the fifth periodic elements are more preferred, and the metal compounds of the fifth periodic elements are even more preferred. Specifically, it is preferred to use calcium compounds, yttrium compounds, and lanthanum compounds, it is more preferred to use calcium compounds and yttrium compounds, and it is particularly preferred to use yttrium compounds.
[0130] The other metal compound is preferably used in a proportion of, for example, 0 to 1.2 mass % (for example, 0 to 1 mol %) relative to the total amount of the above metal compounds used in the mixing step.
[0131] In the method for producing ferrite particles of this embodiment, the amounts of the nickel compound, iron compound, and molybdenum compound used are not particularly limited, but in the raw materials, for example in the mixture, the ratio of the total mass of the nickel compound and the iron compound to the mass of the molybdenum compound may be 0.1 to 40, 0.2 to 20, or 0.4 to 10.
[0132] In the method for producing ferrite particles of this embodiment, when a zinc compound is further blended, the blending amounts of the nickel compound, iron compound, zinc compound and molybdenum compound used are not particularly limited, but in the raw material, for example in the mixture, the ratio of the total mass of the nickel compound, iron compound and zinc compound to the mass of the molybdenum compound may be 0.1 to 40, 0.2 to 20, or 0.4 to 10.
[0133] In the method for producing ferrite particles of this embodiment, the amounts of the manganese compound, iron compound, and molybdenum compound used are not particularly limited, but in the raw materials, for example in the mixture, the ratio of the total mass of the manganese compound and the iron compound to the mass of the molybdenum compound may be 0.1 to 40, 0.2 to 20, or 0.4 to 10.
[0134] In the method for producing ferrite particles of the present embodiment, the molar ratio of nickel to iron (Ni / Fe) in the raw material, for example in the mixture, may be 0.2 to 0.6, or 0.25 to 0.5.
[0135] [Firing process] The calcination step is a step of calcining the mixture. As described above, the manufacturing method of the present embodiment includes calcining the nickel compound and the iron compound in the presence of a molybdenum compound. Alternatively, when a mixture containing a zinc compound is obtained in the mixing step, the calcination step may include calcining the nickel compound and the iron compound in the presence of a molybdenum compound. In addition, when a mixture containing a nickel compound, a manganese compound, and a copper compound and / or a cobalt compound is obtained in the mixing step, the method may include calcining the nickel compound, the manganese compound, the iron compound, and the copper compound and / or the cobalt compound in the presence of a molybdenum compound. In addition, a manganese compound may be used instead of the nickel compound in the mixing step. When a mixture containing a manganese compound, a copper compound and / or a cobalt compound is obtained, the method may include calcining the manganese compound, the iron compound, and the copper compound and / or the cobalt compound in the presence of a molybdenum compound. The ferrite particles according to the embodiment are obtained by firing the mixture. As described above, this manufacturing method is called the flux method.
[0136] The flux method is classified as a solution method. More specifically, the flux method is a crystal growth method that utilizes the fact that the crystal-flux two-component phase diagram shows a eutectic type. The mechanism of the flux method is presumed to be as follows. That is, when a mixture of a solute and flux is heated, the solute and flux become liquid phase. At this time, since the flux is a flux, in other words, since the solute-flux two-component phase diagram shows a eutectic type, the solute melts at a temperature lower than its melting point and forms a liquid phase. If the flux is evaporated in this state, the concentration of the flux decreases, in other words, the effect of the flux in lowering the melting point of the solute is reduced, and the evaporation of the flux becomes the driving force to cause crystal growth of the solute (flux evaporation method). The solute and flux can also cause crystal growth of the solute by cooling the liquid phase (slow cooling method).
[0137] The flux method has the advantages of being able to grow crystals at temperatures much lower than the melting point, being able to precisely control the crystal structure, and being able to form idiomorphic crystals.
[0138] In the production of ferrite particles by the flux method using a molybdenum compound as a flux, the mechanism is not necessarily clear, but it is presumed to be due to the following mechanism, for example. That is, when a nickel compound and an iron compound are fired in the presence of a molybdenum compound, nickel molybdate and iron molybdate are first formed. At this time, as can be understood from the above explanation, the nickel molybdate and iron molybdate grow nickel ferrite crystals at a temperature lower than the melting point of nickel oxide and iron oxide, or nickel ferrite, which is a composite oxide thereof. Then, for example, by evaporating the flux, nickel molybdate and iron molybdate are decomposed, and the crystals grow, thereby obtaining ferrite particles. That is, the molybdenum compound functions as a flux, and nickel ferrite particles are produced via intermediates such as nickel molybdate and iron molybdate.
[0139] The flux method makes it possible to produce ferrite particles that contain molybdenum and in which the molybdenum is unevenly distributed in the surface layer of the ferrite particles.
[0140] The firing method is not particularly limited, and can be performed by a known and commonly used method. When the firing temperature exceeds 800°C, it is considered that the nickel compound, the iron compound, and the molybdenum compound react to form nickel molybdate and iron molybdate. Furthermore, when the firing temperature is 950°C or higher, it is considered that the nickel molybdate and iron molybdate decompose to form nickel ferrite particles. In addition, in the nickel ferrite particles, it is considered that the molybdenum compound is taken into the nickel ferrite particles when the nickel molybdate and iron molybdate decompose to form nickel ferrite and molybdenum oxide.
[0141] In addition, the state of the nickel compound, the iron compound, and the molybdenum compound during firing is not particularly limited, and it is sufficient that the molybdenum compound is present in the same space where it can act on the nickel compound and the iron compound. Specifically, it may be a simple mixing method in which a powder of a molybdenum compound, a powder of a nickel compound, and a powder of an iron compound are mixed together, a mechanical mixing method using a grinder, or a mixing method using a mortar, and it may be mixing in a dry state or a wet state.
[0142] In addition, when the mixture containing the zinc compound is fired, the state of the nickel compound, the iron compound, the zinc compound, and the molybdenum compound is not particularly limited, and the molybdenum compound may be present in the same space where it can act on the nickel compound, the iron compound, and the zinc compound. Specifically, the mixture may be a simple mixture of a powder of a molybdenum compound, a powder of a nickel compound, a powder of an iron compound, and a powder of a zinc compound, a mechanical mixture using a grinder, or a mixture using a mortar, or may be mixed in a dry state or a wet state.
[0143] The firing temperature condition is not particularly limited, and is appropriately determined in consideration of the particle size of the target ferrite particles, the formation of the molybdenum compound in the ferrite particles, the shape of the ferrite particles, etc. The firing temperature may be 950°C or higher, which is close to the decomposition temperature of nickel molybdate and iron molybdate, or may be 1000°C or higher, 1050°C or higher, or 1100°C or higher.
[0144] The higher the sintering temperature, the more easily the particle shape is controlled and the larger the particle size of the ferrite particles is obtained. From the viewpoint of efficiently producing such ferrite particles, the sintering temperature is preferably 950° C. or higher, more preferably 1000° C. or higher, even more preferably 1050° C. or higher, and particularly preferably 1100° C. or higher.
[0145] Generally, in order to control the shape of ferrite particles obtained after sintering or to improve their magnetic properties, sintering at high temperatures above 1200°C, preferably above 1500°C, is necessary. However, there are significant challenges to be overcome in industrial use in terms of the burden on the sintering furnace and energy costs.
[0146] According to one embodiment of the present invention, even under conditions where the maximum sintering temperature for sintering a nickel compound and an iron compound is 1500°C or lower, ferrite particles can be formed efficiently at low cost, which contributes to reducing energy costs and environmental loads.
[0147] Furthermore, according to the method for producing ferrite particles of the embodiment, idiomorphous ferrite particles can be formed regardless of the shape of the precursor even if the firing temperature is 1500° C. or lower, which is a temperature lower than the melting point of iron oxide. From this viewpoint, the firing temperature is preferably 1500° C. or lower, more preferably 1400° C. or lower, even more preferably 1300° C. or lower, and particularly preferably 1200° C. or lower.
[0148] The numerical range of the firing temperature at which the nickel compound and the iron compound are fired in the firing step may be, for example, 800 to 1500°C, 900 to 1500°C, 950 to 1400°C, 1000 to 1300°C, or 1000 to 1200°C.
[0149] From the viewpoint of production efficiency, the temperature rise rate may be 20 to 600° C. / h, 40 to 500° C. / h, or 80 to 400° C. / h.
[0150] Regarding the firing time, the time required to raise the temperature to a predetermined firing temperature is preferably within the range of 15 minutes to 10 hours. The holding time at the firing temperature can be 5 minutes or more, and is preferably within the range of 5 minutes to 1000 hours, and more preferably within the range of 1 to 30 hours. In order to efficiently form ferrite particles, it is more preferable to hold the firing temperature for 2 hours or more, and particularly preferably to hold the firing temperature for 2 to 24 hours.
[0151] As an example, by selecting conditions of a firing temperature of 800 to 1500° C. and a firing temperature holding time of 2 to 24 hours, ferrite particles of the embodiment containing molybdenum can be easily obtained.
[0152] The firing atmosphere is not particularly limited as long as the effects of the present invention can be obtained. For example, an oxygen-containing atmosphere such as air or oxygen, or an inert atmosphere such as nitrogen, argon, or carbon dioxide is preferable, and an air atmosphere is more preferable in terms of cost.
[0153] The calcination apparatus is not necessarily limited, and a so-called calcination furnace can be used. The calcination furnace is preferably made of a material that does not react with the sublimated molybdenum oxide, and it is preferable to use a highly airtight calcination furnace so as to efficiently utilize the molybdenum oxide.
[0154] [Cooling process] The method for producing ferrite particles may include a cooling step, which is a step of cooling the ferrite particles whose crystals have been grown in the firing step.
[0155] The cooling rate is not particularly limited, but is preferably 1 to 1000°C / hour, more preferably 5 to 500°C / hour, and even more preferably 50 to 100°C / hour. A cooling rate of 1°C / hour or more is preferable because the manufacturing time can be shortened. On the other hand, a cooling rate of 1000°C / hour or less is preferable because the firing container is less likely to crack due to heat shock and can be used for a long time.
[0156] The cooling method is not particularly limited, and may be natural cooling or a cooling device may be used.
[0157] [Molybdenum removal process] The method for producing ferrite particles according to the present embodiment may further include, after the firing step, a molybdenum removal step of removing at least a portion of molybdenum, as necessary.
[0158] Methods include washing and high temperature treatment, which may be performed in combination.
[0159] As described above, since molybdenum sublimes during firing, the molybdenum content present in the surface layer of the ferrite particles can be controlled by controlling the firing time, firing temperature, etc., and the molybdenum content and state present in the layers other than the surface layer (inner layer) of the ferrite particles can also be controlled.
[0160] Molybdenum may adhere to the surface of the ferrite particles, and as a means other than the sublimation, the molybdenum may be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, or the like.
[0161] In this case, the molybdenum content in the ferrite particles can be controlled by appropriately changing the concentrations and amounts of water, the aqueous ammonia solution, and the aqueous sodium hydroxide solution used, as well as the cleaning locations and cleaning times.
[0162] As a method for high-temperature treatment, a method in which the temperature is raised to the sublimation point or boiling point of the molybdenum compound or higher can be mentioned.
[0163] [Crushing process] In the sintered product obtained through the sintering step, the ferrite particles may aggregate and may not satisfy the suitable particle size range for the intended application. Therefore, the ferrite particles may be pulverized as necessary to satisfy the suitable particle size range. The method for pulverizing the fired product is not particularly limited, and any conventionally known pulverizing method such as a ball mill, a jaw crusher, a jet mill, a disk mill, a spectromill, a grinder, or a mixer mill can be used.
[0164] [Classification process] The sintered product containing ferrite particles obtained by the sintering step may be appropriately classified to adjust the range of particle sizes. "Classification" refers to an operation of classifying particles into groups according to their sizes.
[0165] The classification may be either a wet type or a dry type, but from the viewpoint of productivity, a dry type classification is preferred. Dry classification includes classification using a sieve as well as wind classification, which classifies based on the difference between centrifugal force and fluid drag. From the viewpoint of classification accuracy, wind classification is preferred, and can be carried out using a classifier such as an air current classifier that utilizes the Coanda effect, a swirling air current classifier, a forced vortex centrifugal classifier, or a semi-free vortex centrifugal classifier.
[0166] The above-mentioned pulverization step and classification step can be carried out at any stage required. Depending on whether or not pulverization or classification is performed and the selection of the conditions therefor, for example, the average particle size of the obtained ferrite particles can be adjusted.
[0167] The ferrite particles of the embodiment, or the ferrite particles obtained by the manufacturing method of the embodiment, are less aggregated or are not aggregated at all, so that they are more likely to exhibit their inherent properties and are more easily handled. In addition, when dispersed in a dispersion medium for use, they are preferred from the viewpoint of having better dispersibility.
[0168] In addition, according to the manufacturing method of ferrite particles of the above embodiment, it is possible to easily manufacture ferrite particles with little or no agglomeration, and therefore has the excellent advantage that ferrite particles having the desired excellent properties can be manufactured with high productivity without performing the above-mentioned crushing and classification processes.
[0169] According to the method for producing ferrite particles of the embodiment described above, it is possible to easily and efficiently produce high-quality ferrite particles that contain molybdenum and have a controlled shape. EXAMPLES
[0170] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.
[0171] <Production of ferrite particles> [Example 1] 5.63g of nickel oxide (Kanto Chemical), 12.45g of iron (III) oxide (Kanto Chemical), 3.6g of molybdenum trioxide (Nippon Inorganic Chemical Industry), and 100g of 5mmφ zirconia beads were charged into an 80ml zirconia pot, and mixed and ground for 60 minutes at 200 rpm using a planetary ball mill (Fritsch, P-5) to obtain a mixture. The resulting mixture was placed in a crucible and fired in a ceramic electric furnace at 1100°C for 10 hours. The temperature was raised at a rate of 5°C / min. After cooling, the crucible was removed and a black powder was obtained. The obtained black powder was transferred to a beaker, 200 g of 0.5% ammonia water was added, and the mixture was stirred and washed for 3 hours to dissolve the remaining molybdenum trioxide. The particles were then filtered by suction filtration using 5C filter paper, and the obtained particles were dried at 120°C to obtain 17.1 g of white powder. The obtained particles were NiF e2 He was O4.
[0172] [Example 2] A black powder was obtained in the same manner as in Example 1, except that the amount of molybdenum trioxide used was 1.8 g.
[0173] [Example 3] 3.19g of nickel oxide (Kanto Chemical Co., Ltd.), 6.81g of iron (III) oxide (Kanto Chemical Co., Ltd. reagent), 13.94g of sodium molybdate dihydrate (Kanto Chemical Co., Ltd. reagent), 8.23g of molybdenum trioxide (Nippon Inorganic Chemical Industry Co., Ltd.) and 100g of 5mmφ zirconia beads were placed in a 100ml polypropylene bottle and mixed and crushed for 120 minutes using a paint shaker (Toyo Seiki Seisakusho Co., Ltd.) to obtain a mixture. The resulting mixture was placed in a crucible and fired at 1300°C for 10 hours in a ceramic electric furnace. The temperature was raised at a rate of 5°C / min. After cooling, the crucible was removed and a black powder was obtained. The black powder obtained was transferred to a beaker, 200 g of ion-exchanged water was added, and the mixture was stirred and washed for 3 hours to dissolve the remaining sodium molybdate. The mixture was then filtered by suction filtration using 5C filter paper, and the obtained particles were dried at 120°C to obtain 9.2 g of black powder. The obtained particles were NiFe2O4.
[0174] [Example 4] A black powder was obtained in the same manner as in Example 3, except that the firing temperature was 1500° C. and the heating rate was 2° C. / min.
[0175] [Example 5] A black powder was obtained in the same manner as in Example 3, except that the firing temperature was 900° C. and the heating rate was 2° C. / min.
[0176] [Example 6] A black powder was obtained in the same manner as in Example 3, except that the firing temperature was 1100°C.
[0177] [Example 7] A black powder was obtained in the same manner as in Example 6, except that the amount of nickel oxide was 3.02 g, and 0.17 g of zinc oxide was further added to the nickel oxide, iron (III) oxide, sodium molybdate dihydrate, and molybdenum trioxide (molar ratio of ZnO to (NiO+ZnO): 0.05). The obtained particles were particles mainly composed of NiZnFe2O4.
[0178] [Example 8] A black powder was obtained in the same manner as in Example 7, except that the amount of nickel oxide charged was 2.86 g and the amount of zinc oxide charged was 0.35 g (molar ratio of ZnO to (NiO+ZnO): 0.1).
[0179] [Example 9] A black powder was obtained in the same manner as in Example 7, except that the amount of nickel oxide charged was 2.23 g and the amount of zinc oxide charged was 1.04 g (molar ratio of ZnO to (NiO + ZnO): 0.3).
[0180] [Example 10] A black powder was obtained in the same manner as in Example 7, except that the amount of nickel oxide charged was 1.59 g and the amount of zinc oxide charged was 1.73 g (molar ratio of ZnO to (NiO + ZnO): 0.5).
[0181] [Example 11] 6.65g of manganese carbonate n-hydrate (Kanto Chemical Co., Ltd.), 8.89g of iron oxyhydroxide (Kanto Chemical Co., Ltd.), 15.5g of sodium molybdate dihydrate (Kanto Chemical Co., Ltd.), 100g of 5mmφ zirconia beads, and 20g of ion-exchanged water were placed in a 100ml polypropylene bottle and mixed and ground in a paint shaker for 120 minutes to obtain a mixture. The mixture was dried at 120°C, placed in a crucible, and fired in an atmospheric electric furnace at 800°C in a nitrogen atmosphere for 10 hours. The temperature was increased at a rate of 5°C / min. After cooling, the crucible was removed to obtain a black powder. The obtained black powder was transferred to a beaker, 200 g of ion-exchanged water was added, and the mixture was stirred and washed for 3 hours to dissolve the remaining sodium molybdate. The mixture was then filtered by suction filtration using 5C filter paper, and the obtained particles were dried at 120°C to obtain a black powder. The obtained particles were mainly composed of MnFe2O4.
[0182] [Comparative Example 1] 5.63g of nickel oxide (Kanto Chemical), 12.45g of iron (III) oxide (Kanto Chemical), and 100g of 5mmφ zirconia beads were placed in an 80ml zirconia pot and mixed and ground for 60 minutes at 200 rpm using a planetary ball mill (Fritsch, P-5) to obtain a mixture. The resulting mixture was placed in a crucible and fired in a ceramic electric furnace at 1100°C for 10 hours. The temperature was increased at a rate of 5°C / min. After cooling, the crucible was removed and 17.5g of black powder was obtained. The particles obtained were NiFe2O4 containing a small amount of unreacted material.
[0183] <Evaluation> The powders obtained in Examples 1 to 11 and Comparative Example 1 were used as sample powders and were evaluated as follows.
[0184] [Crystal structure analysis: XRD (X-ray diffraction) method] The sample powder was filled into a measurement sample holder with a depth of 0.5 mm, which was then set into a wide-angle X-ray diffraction (XRD) device (Rigaku Corporation, Ultima IV) and measurements were performed under the following conditions: Cu / Kα radiation, 40 kV / 40 mA, scan speed 2° / min, and scan range 10 to 70°.
[0185] [Measurement of specific surface area of ferrite particles] The specific surface area of the ferrite particles was measured using a specific surface area meter (Microtrack-Bel, BELSORP-mini), and the surface area per 1 g of sample measured from the amount of nitrogen gas adsorbed by the BET method was defined as the specific surface area (m 2 / g).
[0186] [Primary particle size] Ferrite particles were photographed with a scanning electron microscope (SEM), and for the smallest unit particle (i.e., primary particle) on the two-dimensional image, the maximum length between two points on the contour line of 50 randomly selected primary particles was measured and the average value was taken as the primary particle diameter of the ferrite particles.
[0187] [Particle size distribution measurement] The particle size distribution of the sample powder was measured in a dry state using a laser diffraction type dry particle size distribution analyzer (Japan Laser, HELOS (H3355) & RODOS) under conditions of a dispersion pressure of 3 bar and a suction pressure of 90 mbar. The particle size at the point where the volume cumulative % distribution curve intersects with the horizontal axis at 50% is defined as D. 50 was requested as follows.
[0188] [XRF (X-ray fluorescence) analysis] Using an X-ray fluorescence analyzer (Rigaku Corporation, Primus IV), approximately 70 mg of the sample powder was placed on filter paper, covered with PP film, and XRF (X-ray fluorescence) analysis was performed under the following conditions. Measurement conditions EZ Scan Mode Measuring elements: F~U Measurement time: Standard Measurement diameter: 10mm Balance: None
[0189] The nickel content, iron content, zinc content, and molybdenum content of the ferrite particles obtained by XRF analysis were converted into oxides to obtain the following results: NiO content (Ni1) per 100 mass% ferrite particles, Fe2O3 content (Fe1) per 100 mass% ferrite particles, ZnO2 content (Zn1) per 100 mass% ferrite particles, and MoO3 content (Mo1) per 100 mass% ferrite particles.
[0190] In addition, the manganese content, iron content, and molybdenum content of the ferrite particles obtained by XRF analysis were converted into oxides to obtain the MnO2 content (Mn1) relative to 100% by mass of the ferrite particles, the Fe2O3 content (Fe1) relative to 100% by mass of the ferrite particles, and the MoO3 content (Mo1) relative to 100% by mass of the ferrite particles.
[0191] [XPS surface analysis] Surface elemental analysis of the sample powder was performed using an X-ray photoelectron spectrometer (QUANTERA SXM, manufactured by ULVAC-PHI, Inc.) with monochromated Al-Kα as the X-ray source, and X-ray photoelectron spectroscopy (XPS: X-ray Photoelectron Spectroscopy) was performed. The average value of n=3 measurements was obtained in atom% for each element in an area of 1000 μm square.
[0192] The nickel content, iron content, and molybdenum content in the surface layer of the ferrite particles obtained by XPS analysis were converted into oxides to determine the NiO content (Ni2) (mass %) relative to 100 mass % of the surface layer of the ferrite particle, the Fe2O3 content (Fe2) (mass %) relative to 100 mass % of the surface layer of the ferrite particle, and the MoO3 content (Mo2) (mass %) relative to 100 mass % of the surface layer of the ferrite particle.
[0193] In addition, the manganese content, the iron content, and the molybdenum content in the surface layer of the ferrite particles obtained by XPS analysis were converted into oxides to determine the MnO2 content (Mn2) (mass %) relative to 100 mass % of the surface layer of the ferrite particle, the Fe2O3 content (Fe2) (mass %) relative to 100 mass % of the surface layer of the ferrite particle, and the MoO3 content (Mo2) (mass %) relative to 100 mass % of the surface layer of the ferrite particle.
[0194] [Magnetic analysis] A vibrating sample magnetometer (Riken Denshi, BHV-50) was used to measure the area of 30 mm 2 For a test piece with a thickness of 2.5 mm and a mass of approximately 0.15 g, the magnetic field strength was 7.96×10 4 Measurements were performed at 5 min measurement cycle and 5 A / m.
[0195] <Result> The values obtained from the above evaluations are shown in Table 1. Note that "ND" is an abbreviation for "not detected," indicating that the substance was not detected.
[0196] [Table 1]
[0197] FIGS. 1 to 12 show SEM images of the powders of the above-mentioned Examples and Comparative Examples taken with a scanning electron microscope (SEM). In the powders of Examples 1 to 10, many beautiful polygonal particles were observed, and the crystal shape of the particles was controlled during the manufacturing process (FIGS. 1 to 10). In addition, in the powder of Example 11, many beautiful polygonal particles were observed, and the crystal shape of the particles was controlled during the manufacturing process (FIG. 11). On the other hand, in the powder of Comparative Example 1, amorphous particles with no particular shape were observed (FIG. 12).
[0198] The results of the XRD analysis for Examples 1 to 10 and Comparative Example 1 are shown in Fig. 13. Peaks (unmarked peaks) derived from ferrite (Ni2Fe2O4) were observed in the samples of each Example and Comparative Example. The results of the XRD analysis of Example 11 are shown in Figure 14. Each peak (unmarked peak) derived from ferrite (Mn2Fe2O4) was observed in the sample of this example.
[0199] From the results of the SEM observation and XRD analysis described above, it was confirmed that the powders obtained in the examples and comparative examples were ferrite particles containing ferrite.
[0200] In the sample powders of Examples 1 to 11, almost no peaks derived from impurities were observed (FIGS. 13 to 14, impurity detection "-" in Table 1). On the other hand, in the sample powder of Comparative Example 1, impurities such as nickel oxide and iron oxide, i.e., peaks derived from unreacted raw materials (peaks marked with a circle "●" in FIG. 13) were significantly detected (detection of impurities "+" in Table 1). From this, it was inferred that the ferrite production reaction was not completed in the sample powder of Comparative Example 1, and unreacted substances remained.
[0201] This shows that in each example in which a nickel compound and an iron compound were sintered in the presence of a molybdenum compound, even at a relatively low sintering temperature of 900°C to 1500°C, the ferrite production reaction proceeds well, the content of the above-mentioned impurities is reduced, and high-quality ferrite particles with controlled shapes can be produced with high efficiency.
[0202] In addition, the degree of particle aggregation of each ferrite particle was evaluated based on the SEM observation image according to the following criteria. ++: Particles are aggregated. +: Some aggregation of particles is observed. -: No noticeable aggregation of particles is observed.
[0203] In the ferrite particles of Comparative Example 1, noticeable aggregation and fusion between particles was observed (degree of aggregation: +), whereas in the ferrite particles of Examples 1 to 11, noticeable aggregation was not observed (degree of aggregation: -). This shows that in each example in which either a nickel compound or a manganese compound and an iron compound were calcined in the presence of a molybdenum compound, ferrite particles with low degree of agglomeration or no agglomeration can be easily produced.
[0204] Furthermore, in each Example (see, for example, Examples 3, 5, and 6), there was a tendency that the higher the firing temperature, the larger the particle size of the ferrite particles obtained. In this way, it was found that the particle size of the ferrite particles can be controlled by controlling the sintering temperature, and ferrite particles having a desired particle size can be produced.
[0205] The values of the above NiO content (Ni1), Fe2O3 content (Fe1), ZnO2 content (Zn1), MoO3 content (Mo1), NiO content (Ni2), Fe2O3 content (Fe2), ZnO2 content (Zn2), and MoO3 content (Mo2) are shown in Table 1. Table 1 also shows the values of the MnO2 content (Mn1), Fe2O3 content (Fe1), MoO3 content (Mo1), MnO2 content (Mn2), Fe2O3 content (Fe2), and MoO3 content (Mo2).
[0206] The results of the MoO3 content (Mo1) confirmed that ferrite particles containing molybdenum were obtained.
[0207] From the results of the MoO3 content (Mo2), the ferrite particles of Examples 1 to 11 contain molybdenum in the surface layer, and it is expected that various actions due to molybdenum, such as magnetic properties, will be exhibited.
[0208] Table 1 also shows the calculation results of the surface layer uneven distribution ratio (Mo2 / Mo1) of the MoO3 content (Mo2) to the MoO3 content (Mo1).
[0209] From the results of the surface layer uneven distribution ratio (Mo2 / Mo1), the molybdenum content in the surface layer of the ferrite particles determined by XPS surface analysis is higher than the molybdenum content determined by XRF analysis in the ferrite particles of Examples 1 to 11. This confirms that molybdenum is unevenly distributed in the surface layer of the ferrite particles, and it is expected that various functions due to molybdenum will be effectively exerted.
[0210] In the ferrite particles obtained in Examples 1 and 2 using MoO3 as the raw material, the molybdenum content determined by XRF analysis tended to decrease as the ratio of (Ni compound + Fe compound) / (Mo compound) in the raw material increased. In Examples 3 to 6 using Na2MoO4 in combination with the raw material, when the ratio of (Ni compound + Fe compound) / (Mo compound) in the raw material was constant at 1 / 2, the molybdenum content determined by XRF analysis and the molybdenum content in the surface layer of the ferrite particles determined by XPS surface analysis changed with the change in firing temperature.
[0211] In this way, by controlling the amount or type of the molybdenum compound used or the firing temperature, the amount of molybdenum contained in the ferrite particles can be controlled, and ferrite particles containing the desired amount of molybdenum can be produced.
[0212] In addition, in Examples 7 to 10 in which Na2MoO4 was used in combination with ZnO as the raw material, when the ratio of (Ni compound + Fe compound + Zn compound) / (Mo compound) in the raw materials was constant at 1 / 2, the molybdenum content determined by XRF analysis and the molybdenum content in the surface layer of the ferrite particles determined by XPS surface analysis changed with changes in Ni / Fe.
[0213] The values of the coercive force measured in Examples 2, 10, and 11 are shown in Table 1. The coercive force of the ferrite particles in Examples 2, 10, and 11 was 1.4×10 3A / m or less, which is about 1 / 2 to 1 / 4 lower than in Comparative Example 1, which does not use MoO3 as a raw material, and it was found that a suitable soft ferrite (soft magnetic material) was obtained. On the other hand, the ferrite particles of Comparative Example 1 had a coercive force of 2.5×10 3 A / m, which is a higher value compared to Examples 2, 10, and 11, and it was found that this is unsuitable as soft ferrite.
[0214] The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims.
Claims
1. Ferrite particles containing molybdenum and having a spinel structure, The ferrite particles have a molybdenum content of 0.1 to 30 mass % in terms of a content (Mo 1 ) of MoO 3 relative to 100 mass % of the ferrite particles, as determined by XRF analysis of the ferrite particles.
2. The spinel structure is AFe 2 O 4 2. The ferrite particle according to claim 1, represented by the formula: (wherein A is one or more elements selected from Ni, Mn, Cu, Zn, Mg, Ca, and Co).
3. The molybdenum content in the surface layer of the ferrite particle is determined by XPS surface analysis of the ferrite particle, and is expressed as MoO 3 Concentration rate in terms of Mo 2 The ferrite particles according to claim 1 or 2, wherein the content of the ferrite particles is 2.0 to 95.0 mass%.
4. The MoO content relative to 100 mass% of the ferrite particles is determined by XRF analysis of the ferrite particles. 3 Concentration rate in terms of Mo 1 ) the MoO relative to 100 mass % of the surface layer of the ferrite particle, as determined by XPS surface analysis of the ferrite particle. 3 Concentration rate in terms of Mo 2 ), the surface layer uneven distribution ratio of molybdenum (Mo 2 / Mo 1 3. The ferrite particles according to claim 1, wherein the σ is 1.0 to 80.
5. The ferrite particles according to claim 1 or 2, wherein the average particle size of the primary particles of the ferrite particles is 0.1 to 100 μm.
6. The specific surface area measured by the BET method is 0.1 to 2.5 m 2 The ferrite particles according to claim 1 or 2, wherein the ferrite particles have a molecular weight of 1000 or more and a molecular weight of 1000 or more.
7. 2. A method for producing ferrite particles according to claim 1, comprising calcining a metal compound and an iron compound in the presence of a molybdenum compound, A method for producing ferrite particles, wherein the ratio of the total mass of the nickel compound and the iron compound to the mass of the molybdenum compound in the raw materials is 0.4 to 10.
8. The method for producing ferrite particles according to claim 7 , comprising adding a zinc compound to the metal compound and the iron compound in the presence of the molybdenum compound, and calcining the mixture.
9. 9. The method for producing ferrite particles according to claim 7, wherein the molybdenum compound is at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate and sodium molybdate.
10. The method for producing ferrite particles according to claim 7 or 8, wherein the sintering temperature is 800 to 1500°C.
Citation Information
Patent Citations
Method for reducing power loss of nickel-zinc ferrite by generating nano grain boundary high-resistivity membranes
CN107778001A
Production of nickel - zinc based ferrite
JP2000327411A
Method for producing spinel-type ferrite core and spinel- type ferrite core produced thereby
JP2003321273A
Method for producing forsterite fine particles
JP2016222517A
Silane-treated forsterite microparticles and method for producing the same, organic solvent dispersion of silane-treated forsterite microparticles, and method for producing the same
JP2020100561A
